2003
DOI: 10.1097/01.mp.0000057235.65327.40
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin Alterations in Giant Cell Tumor of Bone

Abstract: Cyclins play an important role in regulating the passage of dividing cells through critical checkpoints in the cell cycle. Because alterations of several cyclins, especially cyclin D1, have been implicated in the development of many human neoplasms, we examined 32 cases of giant cell tumor of long bones for cyclin D1 gene amplification and protein overexpression using differential polymerase chain reaction and immunohistochemistry, respectively. In addition, the expression of cyclin D3, cyclin B1, and the prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
29
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 39 publications
6
29
0
1
Order By: Relevance
“…The percentage of cells expressing cellular staining with the immunohistochemical stain for Ki-67 gives the proliferative index. The index is usually high in aggressive tumors and is regarded as a poor prognostic factor [25,26,27]. In our series, giant cells were Ki-67-negative in all cases and mononuclear cells were Ki-67-positive in various proportions of tumor cells.…”
Section: Discussionmentioning
confidence: 74%
“…The percentage of cells expressing cellular staining with the immunohistochemical stain for Ki-67 gives the proliferative index. The index is usually high in aggressive tumors and is regarded as a poor prognostic factor [25,26,27]. In our series, giant cells were Ki-67-negative in all cases and mononuclear cells were Ki-67-positive in various proportions of tumor cells.…”
Section: Discussionmentioning
confidence: 74%
“…In this regard, it is noteworthy that the association between cyclin D3 and proliferation is likely to be tumor-specific, since it has been previously reported in different types of NHL with the exception of mantle cell lymphoma, 17,34 in pancreatic adenocarcinoma, 38 melanoma 39 and oral dysplastic mucosa, 40 but not in breast carcinoma, 18 gastrointestinal stromal tumor 41 and giant cell tumor of bone. 42 Grade III FLs are biologically distinct from grade I/II FLs 13 and behave aggressively, thus requiring the same therapies as diffuse large B-cell lymphomas (DLBCLs). Accordingly, the prevalence of cyclin D3 IR in grade III FLs in our series is similar to that reported in DLBCLs.…”
Section: Discussionmentioning
confidence: 99%
“…2 In previous studies we observed that the giant cell component of these tumors overexpressed cyclin D1 protein. 3 Compared to the mononuclear component, the giant cells also had higher levels of p21 and more p21 bound to cyclin D1. 4 p21 may explain the cyclin D1 accumulation, but the mechanism leading to increased p21 expression is unknown.…”
mentioning
confidence: 94%